Kesesatan Berpikir dalam Konteks Hukum dan Masyarakat: Studi Kasus Politik Elektoral dan Budaya Media Sosial di Indonesia - Sebastian, Tanius (UI Scholars Hub, 2019)
This article investigates the phenomena of electoral politics and culture of social media in the context of Indonesian law and society through a case study of Jakarta Gubernatorial Election in 2017. The main argument of this article is that the connection between electoral politics and culture of social media shows a fallacious logical thinking in the form of bias and ad populum reasoning. Those two forms of fallacy refer to sectarian politics and ideological polarization. In analyzing the fallacious thinking in some events of the 2017 Jakarta Gubernatorial Election, this article also shows how emotion, anxiety, and hate operate within the reasoning of the relation of the Indonesian state and society. This article primarily aims at identifying the argumentative situation in the case of the 2017 Jakarta Gubernatorial Election, which contains the fallacious thinking. In the end, the ultimate aim is to evaluate an implication that stems from that identification for an adequate conception of legal reasoning in the Indonesian context.